#TITLE_ALTERNATIVE# - (NIM 10105052); Pembimbing: Dr. Agus Yodi Gunawan, LIDIAWATI
Phenomena about thin liquid films are found in our daily life. For example in petroleum industry there is a phenomenon about existence of condensate thin layer in gas transmission pipe. Generally, thin liquid film existence disturbs system and it is necessary to be cleaned from the system. There are two techniques known at present: mechanical scrubing technique and chemical substance addition technique. In this final project, chemical substance addition technique will be studied. Here we consider soluble surfactant as a substance. Using dimensional analysis, lubrication method, perturbation expansion and flattening technique we can formulate mathematical model that represent the dynamic liquid film surface. Application of linear stability analysis indicates that the (in) stability of the system mainly depends on magnitudes of surfactant concentration, the surface tension, and the type of surfactant. More surfactant concentration causes the liquid film unstable. The instability of thin liquid films indicates that the films may be able to be lift up.